Does Play Help to Learn Vocabulary? A Case Study on Primary School Teachers’ Attitude of Dhaka City in Bangladesh - Shirin, Alpona (Universitas Negeri Semarang, 2020)
This study focused on teachers’ attitude towards using games in teaching-learning activities of learning vocabulary. The purpose of this research is to explore teachers’ attitude to the use of a game for learning vocabulary of the students. A qualitative study was conducted with 12 teachers of Azampur Government Primary School of Dhaka city, Bangladesh to gain in depth knowledge of the issues. An everyday game of children named ‘Tic-tac-toe’ was chosen for teachers to teach vocabulary rather traditional process of memorizing. Then, semi-structured focus group interviews were used as tool to collect data from teachers after observing students playing the game. Data was then analyzed for thematic contents by standard content analysis framework which yielded six major themes such as play-based teaching strategy, language development, classroom environment, learning by doing approach, acceptance and barriers on adopting play-based strategy. Overall, findings showed positive attitude towards using game for learning vocabulary of a foreign language. The implications of this study imply that the themes can be effective in classroom practice of Bangladeshi classroom.